Previous Abdomen-Pelvic Surgeries in Infertility patients, their Effects on Tubal Factor Infertility and Safety of Laparoscopy - Shamim Akhtar, Humaira Bibi, Rizwana Nasreen Cheema, Asma Amin Baig, Shagufta Yaqoob, Najia (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To see the types of previous abdomen pelvic surgeries, tubal factor involvement and safety of laparoscopy in infertile patients. Study design: This was a retrospective cross sectional study Place and duration: The study was conducted at Health Care Center Hospital pvt Ltd from July 2020 to June 2022. Methods: All patients with primary or secondary infertility who had history of abdomen- pelvic surgeries were included.Patients who had midline abdominal scar extending above umbilicus were excluded. Data was collected from hospital recordsand analyzed by SPSS version 25. Results: Pelvic adhesions were present in 50(48.5%) patients. Supra pubic transverse incision had 46.7% (24/60)adhesions and 50% (2/4) adhesions were seen in midline incision. 46 (45.06%)patient had tubal pathology.There was no access related injury to omentum or bowel. Access to peritoneal cavity was 100%andnoconversion to laparotomy. There was no delayed complications necessitating to reopen. Conclusion: Laparoscopy is safe in patients who had previous abdominal and pelvic surgery. Microsurgical techniques should be learnt to avoid complications. Keywords: Infertility, Laparoscopy, Abdomen- pelvic surgery, Adhesions.